Q. 65.0( 1 Vote )

# If α, β are roots of x2 – 3x + 2 = 0, form a quadratic equation whose roots are –α and –β

x2 – 3x + 2 = 0 compare this with ax2 – bx + c = 0

a = 1 , b = –3 and c = 2

Here α = –αand β = – β

General form of quadratic equation whose roots are α2 and β2

x2 – (–α – β) x + (–α) (–β) = 0

x2 + (α + β) x + (αβ) = 0

x2 + (3)x + (2) = 0

Therefore, the required quadratic equation is x2 – 3x + 2 = 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Relationship Between Coefficients and Zeros44 mins
Quiz on Important Algebra Questions26 mins
Quiz on Number of Solutions of an Equation24 mins
Interactive Quiz: Algebra Important Questions38 mins
Important Algebra Questions46 mins
Interactive Quiz: Nature of Roots51 mins
Genius Quiz | NTSE Questions Algebra27 mins
Know Some Interesting Proofs in Algebra42 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses